2012
DOI: 10.1002/ijc.27854
|View full text |Cite
|
Sign up to set email alerts
|

Comments on a recent meta‐analysis: Obesity and lung cancer

Abstract: Dear Editor,The role of body mass index (BMI) in relation to lung cancer risk has been the object of considerable interest over the years. For the most part, epidemiologists' primary concern has been to determine whether BMI has an effect on lung cancer that is independent of smoking, a key confounder. We, therefore, read with great interest the quantitative appraisal of the epidemiological evidence on obesity and incidence of lung cancer by Yang et al. 1 Their metaanalysis revealed a significant inverse relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…To date, the relationship between obesity and the incidence of lung cancer remains unclear (72). Controversy still focuses on the effect of smoking in studies investigating the relationship between BMI and lung cancer (73). In case–control studies, odds ratios for lung cancer by levels of BMI showed an increasing linear trend with a lower threshold BMI for current smokers and ex-smokers of both sexes (74, 75).…”
Section: Relationship Between Obesity and Cancermentioning
confidence: 99%
“…To date, the relationship between obesity and the incidence of lung cancer remains unclear (72). Controversy still focuses on the effect of smoking in studies investigating the relationship between BMI and lung cancer (73). In case–control studies, odds ratios for lung cancer by levels of BMI showed an increasing linear trend with a lower threshold BMI for current smokers and ex-smokers of both sexes (74, 75).…”
Section: Relationship Between Obesity and Cancermentioning
confidence: 99%
“…A meta-analysis by Yang et al found that excess body weight was inversely associated with incidence of NSCLC [27]. This study, however, was criticized for large heterogeneity of results, lack offormal evaluation of study quality, and confounding by smoking [28]. The association of increased BMI and NSCLC survival is not as well defined in the literature as the data on BMI and risk of developing NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the authors concluded that the heterogeneity they found is related to the lack of technical standardization, there is no mention on the clinical consequences. We thus suggest that research should be improved by using well-defined methods for assessing the quality of articles (e.g.…”
Section: (The Editors Do Not Hold Themselves Responsible For Opinionsmentioning
confidence: 99%